THE INFLUENCE OF TASTE, BRAND IMAGE, AND SOCIAL MEDIA MARKETING ON CONSUMER SATISFACTION AT SOTO KAPULOGO RESTAURANT - Madeline Fanny Effensia; Feliciana Sulimto; J.E Sutanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This research focuses on evaluating how taste, brand image, and social media marketing collectively influence consumer satisfaction at Soto Kapulogo restaurant in Surabaya. Utilizing a quantitative methodology, empirical data were gathered through instrument administered to a sample of 163 participants. A purposive sampling technique, within a non-probability framework, was utilized to select respondents based on specific criteria: a minimum of two visits to the restaurant, an age range of 17–31 years, and an active Instagram account. To examine the influence between variables, this study applied multiple linear regression techniques facilitated by SPSS software. Empirical findings confirm that all three independent variables significantly influence consumer satisfaction, both partially and simultaneously, with the regression model accounting for 55.3% of the observed variance. These findings suggest that prioritizing flavor quality, brand identity, and digital engagement is vital for bolstering customer satisfaction. Additionally, this research supports the advancement of SDG 8 by fostering economic growth within the culinary sector.